2008
DOI: 10.1111/j.1365-2249.2008.03599.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of taurine on oxidative stress and apoptosis-related protein expression in trinitrobenzene sulphonic acid-induced colitis

Abstract: SummaryUlcerative colitis (UC) is a multi-factorial inflammatory disease of the colon and rectum. The present study was undertaken to investigate the effect of taurine, an anti-oxidant amino acid, on oxidative stress and the expression of apoptosis-related proteins, pro-apoptotic Bax and anti-apoptotic B cell lymphoma-2 (Bcl-2) in colon tissue in rats with 2,4,6-trinitrobenzene sulphonic acid (TNBS)-induced colitis. Rats received taurine (1·5% w/v) in drinking water for 15 days before and 15 days after adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 38 publications
4
32
1
Order By: Relevance
“…This concurs with the high levels of taurine, as taurine has been shown to possess antioxidant, antiapoptotic and anti-inflammatory effects. 32 Surprisingly, glutamine, glutamate, glutathione, and ascorbate were found not to be elevated in the colonocytes from patients with active UC compared to controls, and glutamine was even found with a trend toward reduced levels. Two important notions can be made from this observation: one, the increased levels of glutamine and glutathione found in the biopsies from patients with active UC are most likely due to activated lymphocytes in the lamina propria, as these metabolites were prominent features of the metabolic profile of peripheral lymphocytes ( Figure 1E); two, it raises the question of this circumstance being a part of the pathophysiology of UC, as it has been proposed that gut mucosal turnover and barrier function is compromised due, in part, to relative glutamine and glutathione deficiency.…”
Section: Discussionmentioning
confidence: 92%
“…This concurs with the high levels of taurine, as taurine has been shown to possess antioxidant, antiapoptotic and anti-inflammatory effects. 32 Surprisingly, glutamine, glutamate, glutathione, and ascorbate were found not to be elevated in the colonocytes from patients with active UC compared to controls, and glutamine was even found with a trend toward reduced levels. Two important notions can be made from this observation: one, the increased levels of glutamine and glutathione found in the biopsies from patients with active UC are most likely due to activated lymphocytes in the lamina propria, as these metabolites were prominent features of the metabolic profile of peripheral lymphocytes ( Figure 1E); two, it raises the question of this circumstance being a part of the pathophysiology of UC, as it has been proposed that gut mucosal turnover and barrier function is compromised due, in part, to relative glutamine and glutathione deficiency.…”
Section: Discussionmentioning
confidence: 92%
“…Immune modulation was demonstrated by experimental studies that localized membrane progesterone receptors (mPRs) on CD4 and CD8 T-lymphocytes 3 . Moreover it has been experimentally confirmed that progesterone inhibits the development of oxygen-centered free radicals and prevents cell damage after development of benzene induced toxicity as shown from the levels of lipid peroxidation (malondialdehit), glutathione (GSH) and cytochrome P450 2E1 in the liver and kidney tissues 4 .…”
Section: Introductionmentioning
confidence: 99%
“…One candidate agent is progesterone which was found to depress the inflammatory response and reduce the cell membrane damage caused by lipid peroxidation and development of free radicals [2][3][4] . Immune modulation was demonstrated by experimental studies that localized membrane progesterone receptors (mPRs) on CD4 and CD8 T-lymphocytes 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with urokinase alone was effective in reducing infarct volume at 4, 6 h but not 8 h after ischemia, incidence of hemorrhagic transformation were increased along with delayed thrombolysis treatment. When perfusion was recovered after administration of urokinase, it made taurine more easily access to ischemic tissue, the entering taurine could attenuate inflammatory reaction, oxidative stress, disruption of brain blood barrier and apoptosis [14,[30][31][32][33][34], finally extended the therapeutic window until to 8 h after the onset, which would lead to an increased number of patients being eligible for thrombolytic therapy.…”
Section: Discussionmentioning
confidence: 99%